Investigating controlled teleportation capability of quantum states with respect to k-separability - Choi, Minjin; Shin, Jeonghyeon; Lee, Gunho; Bae, Eunok (American Physical Society, 2024)
Quantum teleportation is an essential application of quantum entanglement. The examination of teleportation fidelity in two-party standard teleportation schemes reveals a critical threshold distinguishing separable and entangled states. For separable states, their teleportation fidelities cannot exceed the threshold, emphasizing the significance of entanglement. We extend this analysis to multiparty scenarios known as controlled teleportation. Our study provides thresholds that N -qudit k -separable states cannot exceed in a controlled teleportation scheme, where N ?, 3 and 2 k N . This not only establishes a standard for utilizing a given quantum state as a resource in controlled teleportation but also enhances our understanding of the influence of the entanglement structure on controlled teleportation performance. In addition, we show that genuine multipartite entanglement is not a prerequisite for achieving a high controlled teleportation capability.